Differences in Risk Factor of Cardiovascular Disease Risk on Rural and Urban Population - Rosjidi, Cholik Harun; Wahyuni, Nurul Sri; Isro’in, Laily (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Cardiovascular disease is a global threat. This study aimed to obtain a description of cardiovascular disease pattern among rural and urban population in Ponorogo. Two locations were chosen to represent rural and urban area through cluster sampling. Cross sectional study design was chosen with a sample size of 350 respondents. The research instrument was adopted from WHO STEPS. Difference in prevalence between the two clusters were analyzed with ?2 test, with ?=0.05. The result showed that the prevalence smoking and alcohol consumption among males were higher in rural than urban population (p= 0.04 and p=0.012 respectively). The prevalence of unhealthy fruit consumption was higher in both sexes from rural population (p =0.025 and p=0.012). Hypertension was higher among rural female compared to female living in urban area (p=0.024).